Journal of Cellular Biochemistry: Volume 115, Number 12, December, 2014. Issue 12 (15th October 2014) - Unknown
<x xml:space="preserve">Abstract</x> Cover: Maximum intensity projection images from a control mouse (left) and a mouse challenged with ovalbumin (right), both exposed to room air. Mouse lung images were provided by Dr. Lennart K. Lundblad, Department of Medicine, University of Vermont College of Medicine. See article by Chapman et al. on pages 2055–2064.